2016
DOI: 10.1038/bjc.2016.362
|View full text |Cite
|
Sign up to set email alerts
|

The FOXD3/miR-214/MED19 axis suppresses tumour growth and metastasis in human colorectal cancer

Abstract: Background: MiR-214 is aberrantly regulated in several tumours, but its underlying mechanisms in colorectal cancer (CRC) metastasis remain largely unknown. This study aimed to demonstrate the function and potential mechanism of miR-214 in regulating invasion and metastasis of CRC. Methods:The transcription factor and targets of miR-214 were predicted by bioinformatics and validated using ChIP and dual-luciferase reporter assay. DNA methylation status was explored using bisulphite sequencing PCR. The in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 53 publications
0
48
0
Order By: Relevance
“…Several studies have proposed that mRNAs and lncRNAs can regulate each other through their capacity to compete for miRNA binding [17,18]. In this study, for the first time, we reported that KCNQ1OT1 plays an important role in cataract formation.…”
Section: Discussionmentioning
confidence: 57%
“…Several studies have proposed that mRNAs and lncRNAs can regulate each other through their capacity to compete for miRNA binding [17,18]. In this study, for the first time, we reported that KCNQ1OT1 plays an important role in cataract formation.…”
Section: Discussionmentioning
confidence: 57%
“…Previously, miR‐214 was reported to function as a tumor suppressor in colon cancer (11, 44, 45). miR‐214 inhibits colon cancer proliferation and migration via the suppression of ARL2 (44) and HMGA1 (45).…”
Section: Discussionmentioning
confidence: 99%
“…miR‐214 inhibits colon cancer proliferation and migration via the suppression of ARL2 (44) and HMGA1 (45). miR‐214/ MED19 axis suppresses tumor growth and metastasis in human CRC (11). In the present study, we found that miR‐214 levels were remarkably decreased in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study may also have implications for MED19 function in other cancers. For example, reduction of MED19 by siRNA has been reported to reduce the proliferation of certain breast, ovarian, cervical, and lung cancer cell lines, and increased abundance of MED19 protein is observed in tumors relative to benign tissue [55–62]. This suggests that MED19 functions with other transcription factors in other cell types to regulate gene expression and enhance cellular proliferation.…”
Section: Discussionmentioning
confidence: 99%